Perceptions Toward the Effectiveness of MOOCs: A Case Study of Afghan Postgraduate Students at UiTM, Malaysia - Hazrat Usman Mashwani; Izaham Shah Ismail (IJECA (International Journal of Education and Curriculum Application), 2024)
The use of technology in education is inevitable in the current era of quality education. The technology works as a backbone of the modern education system and without technology, the modern education would have never achieved the current success. Massive Open Online Course (MOOC) is one of the best examples of modern instructional technology in education. MOOC has made the current education so vivid and accessible that anyone, anytime from anywhere can follow the classes as the traditional student does. As technology is a big issue in Afghanistan, so it has hindered the use of MOOCs in the educational system of Afghanistan. However, a great number of Afghan students regularly go abroad for their higher studies where they come across with the use of MOOCs. This study aims to investigate the perceptions of Afghan postgraduate students at Universiti Teknologi Mara (UiTM) toward the effectiveness of MOOCs. The study has specifically investigated the perceptions of Afghan postgraduate students at UiTM toward MOOCs and the challenges students face while using MOOCs for learning. A qualitative research approach was used for the study. The data collected through semi-structured interviews was thematically analysed and presented. Overall, 5 participants participated in the study. The findings revealed that participants had positive views towards the use of MOOCs and considered MOOCs as the best source of learning. Unreliable uploaded materials, technical issues of the MOOC's software and students' lack of proper knowledge to use MOOCs were some of the leading challenges while using MOOCs.